Adultização infantil e sua relação com as mídias digitais - Ambrosini, Andressa Pietrobon (My University, 2022)
This work addresses the theme "Child Adultization and its relationship with digital media" which is aligned with the objective of investigating the role of digital media in the adultization process of children, as well as evaluating the consequences of these transformations within the field of human development and children's behavior. Therefore, this investigation sought to respond to the following research problem: "What is the influence of digital media on the adultization process of children in contemporary times?" The research described is of an applied nature, qualitative in approach, exploratory in relation to its objectives, in the field modality, it was developed through the Case Study methodology (GIL, 2008), with application of semi-structured interviews, applied to a group of families. The data collected through these interviews were analyzed through discursive textual analysis (MORAES, 2003) and based on theoretical contributions, among which I highlight Áraujo, Niebuhr and Aguiar (2019), Piaget (1970), Vygotsky (1987) - (1989 ). Erbolato (1985) , Moran (2000 and 2009), Cannan, Ribeiro and Paola (2017), Nunes and Silveira (2015). From the data analysis it was possible to identify the following blocks of study: Digital media and its relationship with the pedagogical process, Families and their relationship with digital media and The influence of media on children's development as an adultization process . The study allowed for the construction of some knowledge that allowed a deeper reflection on childhood and child development in contemporary times, with a focus on the use of technology. It also allowed for the recognition of the need for a careful look by the school and the family on how this access is occurring, as exposure without criteria to the multiplicity of digital media available on the network can trigger early adolescence, which causes the loss of childhood, socialization and most importantly, the stage of the child's purity in his childhood, leading to his adultization. Considering the complexity of the topic in focus, the study promoted a lot of learning, but it also triggered some concerns which are shared throughout the text. [resumo fornecido pelo autor]
O presente trabalho aborda o tema "Adultização Infantil e sua relação com as mídias digitais" que está alinhado ao objetivo de investigar qual o papel das mídias digitais no processo de adultização, das crianças, bem como avaliar as consequências destas transformações dentro do campo de desenvolvimento humano e comportamental das crianças. Para tanto, a referida investigação buscou dar resposta ao seguinte problema de pesquisa: "Qual a influência das mídias digitais no processo de adultização das crianças na contemporaneidade? " A investigação descrita é de natureza aplicada, qualitativa quanto à abordagem, exploratória em relação aos seus objetivos, na modalidade de campo, foi desenvolvida através da metodologia de Estudo de Caso (GIL, 2008), com aplicação de entrevistas semiestruturadas, aplicadas a um grupo de famílias. Os dados coletados através das referidas entrevistas foram analisados por meio da análise textual discursiva (MORAES, 2003)e fundamentados em aportes teóricos entre os quais destaco Áraujo, Niebuhr e Aguiar ( 2019), Piaget (1970), Vygotsky (1987) - ( 1989). Erbolato (1985), Moran (2000)- (2009), Cannan, Ribeiro e Paola (2017), Nunes e Silveira (2015). A partir da análise dos dados foi possível fazer a identificação dos seguintes blocos de estudo: As mídias digitais e sua relação com o processo pedagógico, As famílias e sua relação com as mídias digitais e A influência das mídias no desenvolvimento das crianças enquanto processo de adultização. O estudo permitiu a construção de alguns conhecimentos que possibilitaram reflexão aprofundada acerca da infância e do desenvolvimento infantil na contemporaneidade, com enfoque na utilização da tecnologia. Ainda, possibilitou o reconhecimento da necessidade de um olhar atento da escola e da família sobre a forma de como este acesso está ocorrendo, pois a exposição sem critérios à multiplicidade de mídias digitais disponíveis na rede pode desencadear um adolescimento precoce, que provoca a perda da infância, da socialização e do mais importante, a fase da pureza da criança em sua infância, levando a sua adultização. Considerando a complexidade da temática em foco, o estudo promoveu muitas aprendizagens, mas também desencadeou algumas preocupações as quais são compartilhadas ao longo do texto. [resumo fornecido pelo autor]
Keywords: Educação de crianças; Crianças - Desenvolvimento; Mídia digital; Famílias